Familial risks between giant cell arteritis and Takayasu arteritis and other autoimmune diseases in the population of Sweden - Thomsen, Hauke; Li, Xinjun; Sundquist, Kristina; Sundquist, Jan; Försti, Asta; Hemminki, Kari (Scientific reports, 2020)
Giant cell arteritis (GCA, also called temporal arteritis) is a rare and Takayasu arteritis (TA) is an even rarer autoimmune disease (AID), both of which present with inflammatory vasculitis of large and medium size arteries. The risk factors are largely undefined but disease susceptibility has been associated with human leukocyte antigen locus. Population-level familial risk is not known. In the present nation-wide study we describe familial risk for GCA and for GCA and TA with any other AID based on the Swedish hospital diagnoses up to years 2012. Family relationships were obtained from the Multigeneration Register. Familial standardized incidence ratios (SIRs) were calculated for offspring whose parents or siblings were diagnosed with GCA, TA or any other AID. The number of GCA patients in the offspring generation was 4695, compared to 209 TA patients; for both, familial patients accounted for 1% of all patients. The familial risk for GCA was 2.14, 2.40 for women and non-significant for men. GCA was associated with 10 other AIDs and TA was associated with 6 other AIDs; both shared associations with polymyalgia rheumatica and rheumatoid arthritis. The results showed that family history is a risk factor for GCA. Significant familial associations of both GCA and TA with such a number of other AIDs provide evidence for polyautoimmunity among these diseases.
Keywords: Polymyalgia Rheumatica; Švédsko; Arthritis, Rheumatoid; Female; rodina; revmatoidní artritida; Takayasuova arteriitida; Autoimmune Diseases; ženské pohlaví; Takayasu Arteritis; anamnéza; lidé; Giant Cell Arteritis; genetická predispozice k nemoci; Genetic Predisposition to Disease; autoimunitní nemoci; Male; Sweden; riziko; polymyalgia rheumatica; Medical History Taking; Family; obrovskobuněčná arteritida; mužské pohlaví; Risk; Humans